From traditional remedy to modern therapy: a comprehensive review of palmatine’s multi-target mechanisms and ethnopharmacological potential - Shi, Zhoujing; Han, Lutuo; Yang, Huasen; Lu, Geling; Shi, Zhouying; Ma, Boyan (Frontiers in Pharmacology, 2025)
BackgroundAs a core active metabolite of traditional Chinese medicines including Coptis chinensis Franch. and Phellodendron amurense Rupr., palmatine has been employed in Asian traditional medicine for centuries, primarily for treating jaundice, liver diseases, and inflammatory disorders. Modern research reveals that this isoquinoline alkaloid exhibits multi-target regulatory properties, demonstrating broad therapeutic potential across various diseases. This review systematically elucidates the molecular mechanisms of palmatine in treating digestive system disorders, neurological diseases, metabolic diseases, cancer and so on and cancers, with particular emphasis on analyzing its “disease-target-pathway” relationships.MethodsIn accordance with the PRISMA guidelines, a comprehensive literature search was conducted using PubMed, Web of Science, and Embase databases. The search terms included “Palmatine,” “Disease,” “in vitro/in vivo experiment,” “Inflammation,” “Anti-inflammatory,” and “Antioxidation.” among others. The search covered all English-language articles related to palmatine published between 1 January 2014, and 31 May 2025. All included studies underwent a quality assessment.ResultsStudies demonstrate palmatine’s multi-target mechanisms through regulation of NF-κB/NLRP3, Nrf2/HO-1, and AMPK/mTOR signaling pathways, mediating anti-inflammatory, antioxidant, and metabolic-modulating effects. Its exceptional blood-brain barrier permeability confers distinct advantages for central nervous system disorders, while its metabolites such as 8-oxypalmatine display superior bioactivity. In anticancer applications, palmatine functions through multiple mechanisms encompassing direct tumor cell cytotoxicity, metastasis suppression, and angiogenesis inhibition, while maintaining dose-dependent safety characteristics.ConclusionPalmatine serves as a bridge connecting traditional medicine and modern therapy, offering novel strategies for complex diseases through its polypharmacological actions. Although limited by low bioavailability, clinical potential can be enhanced via combination therapies, structural modifications such as C13 alkylation, and nano-delivery systems. Future research should prioritize exploration of synergistic effects, targeted delivery technologies, and large-scale clinical validation.